Investigating the Simultaneity of Corporate Hedging and Debt Policies: Empirical Evidence from Indonesia - Suriawinata, Iman Sofian (Gadjah Mada International Journal of Business, 2005)
The primary objective of this paper is to investigate the simultaneity of corporate hedging and debt policies. Using a pooled sample of Indonesian non-financial listed firms covering the periods of 1996-2001, the present study finds evidence that corporate hedging and debt policies are simultaneously determined. That is, the use of debts motivate firms to hedge; but simultaneously, hedging increases debt capacity and induces firms to borrow more in order to take advantage of the tax benefits arising from additional debt capacity. Another important finding is that financially distressed firms âas indicated by their debt restructuring programsâ are less motivated to hedge, because such firms will see that the option values of their equity will increase as their cash-flow volatilities increase. Therefore, financially distressed firms tend not to hedge; or at least, hedge lesser compared to those of firms that do not experience financial distress.